PROPERTIES AND STRUCTURAL BEHAVIOR OF SAWDUST INTERLOCKING BRICK - , VETHAMOORTY (IRC, 2015)
Bricks are broadly utilized in construction and building material around the globe. Conventional bricks are delivered from clay with high temperature kiln firing or from ordinary Portland cement concrete, and in this manner contain high embodied energy and have large carbon footprint. In numerous territories of the world, there is now a lack of natural resource for the generation of bricks. This paper presents a state-of-the-art review of research on sawdust in production of interlocking brick. Besides that this paper also justifies the properties and structural behavior of sawdust interlocking brick. For the study purpose, 24 mixtures were prepared by varying the percentage of sawdust (0%-100%) and other cementitious materials. The sawdust interlocking brick mixture consists of Sawdust, Sand, Ordinary Portland Cement, Fly Ash, Nano-silica and water. From each mixture, the final product was tested for compressive strength after 7 days of curing. The mixture with an optimum compressive strength was chosen and following experimental tests were conducted. The laboratory experiments are conducted to evaluate Modulus of Rapture, Initial Rate of Absorption, 5 and 24 hour Absorption and Dimensional Tolerance. All the test conducted are based on the American Standard Testing Method (ASTM). The study revealed a good quality of sawdust interlocking brick can be produced, whereby contributing to sustainable development